Molecular Process of Stem Cells in Modern Biology - Amina Shahid, Haris Abdul Rehman, Noorulain Hyder, Sohail Ahmad, Mah Noor Hassan, Maria, Sulaiman Shams, Shahid Mehmood, Hisamuddin Shaikh, Muhammad Rafiq (Pakistan Journal of Medical & Health Sciences, 2022)
Stem cells have a wide range of traits, including the ability to self-renewal and differential interactions between various cell types that vary with their location within tissue and their immediate surroundings. Inhibitors of both are influenced by the cell cycle, genes involved in chromosomal rearrangements, critical developmental proteins, and signaling pathways. Wnt, Notch, Hedgehog Pathways, BMI-1, OCT3/4, ARF, NANOG, p16Ink4a, and this includes HOXB4, SOX2, and their homologous paralog, govern self-renewal. Stem cells and their molecular pathways that regulate self-renewal and differentiation hold great promise for theoretical and practical studies. Keyword: gene regulation of stem cell self-renewal and differentiation genes for BMI-1, NANOG, OCT3, OCT4, p16Ink4a, SOX2, microenvironment, ARF protein proteins 1 (hedgehog), proteins 2 (Wnt.), and receptors 3 (notch).